Home dental bleaching monitored with microelectronic sensors to record the wearing times of an acetate tray/bleaching product - Pavani, C. C. [UNESP]; Sundfeld, D.; Schott, T. C.; Bertoz, A. P.M. [UNESP]; Bigliazzi, R. [UNESP]; Sundfeld, R. H. [UNESP] (Operative Dentistry, 2018)
The present case study quantifies the clinical wearing time of an acetate tray/bleaching product during home dental bleaching. The patient was instructed to use a 10% carbamide peroxide gel for 6-8 hours each day for 20 days. The wearing time of the tray was measured by a microsensor from TheraMon microelectronic system (Sales Agency Gschladt, Hargelsberg, Austria) completely embedded in the tray so that the clinician would be informed as to the precise time the tray was placed in the mouth. Evaluation of the daily printout during dental bleaching demonstrated that the patient did not correctly follow the clinician's instructions as to the wearing time of the tray. Recording the wearing time of dental bleaching agents can be beneficial for both dental professional and patient to obtain a more effective treatment according to the patient's needs and expectations.